The Effect of Replacing Wheat Flour with Quinoa Flour (Chenopodium quinoa) in the Production of Odading on Acceptability, Protein Content, and Moisture Content - Diel Piero Junior; Muhammad Ansori (PT FORMOSA CENDEKIA GLOBAL, 2026)
This research investigated how replacing wheat flour with quinoa flour influenced the sensory acceptance, protein concentration, and moisture level of odading. The experiment applied a single-factor completely randomized design consisting of four formulations. The formulations were F1 without quinoa flour, F2 with 10% quinoa flour, F3 with 20% quinoa flour, and F4 with 30% quinoa flour. Sensory evaluation was performed through a hedonic test involving 40 untrained panelists. Each panelist assessed the appearance, aroma, flavor, and texture of the products using a nine-point preference scale. Differences in sensory scores among the formulations were examined using the Kruskal–Wallis test. When significant differences were identified, further comparisons were conducted using the Mann–Whitney test at a significance level of p<0.05. Laboratory measurements of protein and moisture were performed at the SIG Laboratory in Semarang. The findings indicated that the proportion of quinoa flour significantly influenced product appearance (p<0.001) and aroma (p=0.005). In contrast, no statistically significant differences were found in flavor (p=0.620) or texture (p=0.368). A gradual increase in protein was observed as more quinoa flour was incorporated. Protein content rose from 7.90% in the control formulation to 9.20% in the formulation containing 30% quinoa flour. The moisture values varied between 23.13% and 30.42%, with F2 showing the highest moisture content. These findings demonstrate that incorporating quinoa flour at levels of up to 30% can improve the protein content of odading while maintaining consumer acceptance of its flavor and texture. Nevertheless, higher quinoa flour proportions may produce noticeable changes in appearance and aroma.